The role of genetic variability of the host on the resistance to Neospora caninum infection in cattle - Dinon, María Anabella; Fiorani, Franco; Campero, Lucia Maria; Moore, Prando Dadin; Corva, Pablo (Wiley, 2024)
Neospora caninum is one of the most frequently diagnosed abortifacient pathogens in cattle. There is abundant genomic information about the parasite itself, but very little is known about the genetic variability of resistance in the most common intermediate host. The aim of this review was to compile all the available information about the genetic variability associated with the resistance to N. caninum both between and within cattle breeds. We systematically searched for published studies that investigated the influence of genetics of the host on the prevalence of N. caninum and risk of abortion. Beyond the potential confounding effects of feeding systems, management and animal density, some lines of evidence suggest that Holstein, the most popular breed for milk production, has a comparatively higher risk of abortion due to infections by N. caninum, whereas some beef breeds from Continental Europe seem to be more resistant. It is still not clear if different genetic mechanisms of resistance are involved in the two known routes of infection: postnatal ingestion of oocysts or transplacental transmission from the infected dam to the fetus. Genomic information associated with susceptibility to infection and risk of abortion in different cattle breeds is still scarce. The information reported here could be useful to identify new research alternatives and to define novel strategies to deal with this major problem of animal production.